Short-term surgical outcomes of laparoscopy-assisted versus totally laparoscopic Billroth-II gastrectomy for gastric cancer: a matched-cohort study - Ji-Hyun Kim; Kyong-Hwa Jun; Hyung-Min Chin (BMC Surgery, 2017)
Abstract Background To evaluate feasibility and benefits of intracorporeal anastomosis, we compared short-term surgical outcomes between laparoscopy-assisted distal gastrectomy (LADG) and totally laparoscopic distal gastrectomy (TLDG) with Billroth-II (B-II) anastomosis for gastric cancer. Methods Sixty patients underwent attempted B-II TLDG from 2011 through 2013. Patients who underwent B-II LADG prior to 2011 were matched to TLDG cases for demographics, comorbidities, tumor characteristics, and TNM stage. Perioperative and short-term surgical outcomes were compared between the two groups. Results Clinicopathological characteristics of both groups were comparable. The B-II TLDG group had a shorter hospital stay (9.4 vs. 12.0 days, P = 0.038) and average incision size was smaller (3.5 vs. 5.4 cm, P = 0.030) than in the B-II LADG group. Anastomotic leakage was not recorded in either group, and there were no differences in the rates of perioperative complications and in inflammatory parameters between the two groups. Conclusions This study suggests that B-II TLDG is feasible, compared to B-II LADG, and that it has several advantages over LADG, including a smaller incision, a shorter hospital stay, and more convenience during surgery. However, prospective randomized controlled studies are still needed to confirm that B-II TLDG can be used as a standard procedure for LDG.